(untitled) (FuLiA/UFMG, 2021)
This article discuss João Havelange’s ideology and political action. In general, traditional biographies about the Brazilian leader emphasize the innovative and distinctive character of João Havelange’s life. Contrary to this narrative, this article intends to insert Havelange’s ideas in the very context in which they were disseminated and produced. In this sense, far from constituting an atypical and singular case, Havelange’s trajectory is perceived as a methodological tool to understand more comprehensive characteristics of the group in which he represents – the football presidents and the political elite in Rio.